Regulatory T cells and IFN-γ-producing Th1 cells play a critical role in the pathogenesis of Sjögren's Syndrome - Wang, Yin-Hu; Li, Wenyi; McDermott, Maxwell; Son, Ga-Yeon; Maiti, George; Zhou, Fang; Tao, Anthony; Raphael, Dimitrius; Moreira, Andre L; Shen, Boheng; Vaeth, Martin; Nadorp, Bettina; et al. (bioRxiv, 2024)
Sjögren's Disease (SjD) is an autoimmune disorder characterized by progressive dysfunction, inflammation and destruction of salivary and lacrimal glands, and by extraglandular manifestations. Its etiology and pathophysiology remain incompletely understood, though a role for autoreactive B cells has been considered key. Here, we investigated the role of effector and regulatory T cells in the pathogenesis of SjD. Histological analysis, RNA-sequencing and flow cytometry were conducted on glands, lungs, eyes and lymphoid tissues of mice with regulatory T cell-specific deletion of stromal interaction proteins (STIM) 1 and 2 ( ), which play key roles in calcium signaling and T cell function. The pathogenicity of T cells from mice was investigated through adoptively transfer into lymphopenic host mice. Additionally, single-cell transcriptomic analysis was performed on peripheral blood mononuclear cells (PBMCs) of patients with SjD and control subjects. mice develop a severe SjD-like disorder including salivary gland (SG) and lacrimal gland (LG) inflammation and dysfunction, autoantibodies and extraglandular symptoms. SG inflammation in mice is characterized by T and B cell infiltration, and transcriptionally by a Th1 immune response that correlates strongly with the dysregulation observed in patients with SjD. Adoptive transfer of effector T cells from mice demonstrates that the SjD-like disease is driven by interferon (IFN)-γ producing autoreactive CD4 T cells independently of B cells and autoantiboodies. scRNA-seq analysis identifies increased Th1 responses and attenuated memory Treg function in PBMCs of patients with SjD. We report a more accurate mouse model of SjD while providing evidence for a critical role of Treg cells and IFN-γ producing Th1 cells in the pathogenesis of SjD, which may be effective targets for therapy.